Considerations on the Translation of Introductory Coursebooks: The Need for an Interdisciplinary Approach - Nunez-Becerra, S (PONTIFICIA UNIV CATOLICA CHILE, FAC LETRAS, 2020)
Scientific discourse in any language must meet three principles: veracity, accuracy and clarity (Navarro, ma; Corral & Encinas, 2013). However, texts fulfilling these three principles are not quite frequent in Spanish. In scientific texts, linguistic features are considered less important and often dismissed because of both the referential function of these texts and the fact that they are mainly addressed to experts in a certain field. This scenario is not very different when it comes to scientific translation into Spanish, which is performed almost exclusively by scientists (Gutierrez, 1998; Claros, 2016). However, scientific texts are not addressed to experts only. One example is the genre of introductory coursebooks at university, whose receivers are just starting to study the subject in depth. Since introductory coursebooks are defined as a fundamental means to access to specialized knowledge in higher education (Parodi, 2008), achieving the principles of the scientific discourse turns out to be essential for the appropriate comprehension of these texts and eventually for the students academic success. The present work seeks to question the simplistic view of language as a mere instrument in the context of scientific translation into Spanish as well as to analyze some of its implications in education. To this end, I have selected some passages from an introductory coursebook on biochemistry and its official translation into Spanish. Thus, this article intends to shed some light on the importance of an interdisciplinary approach in translation in order to achieve the scientific language principles.